Future scenarios as an instrument for forest management: manual for training facilitators of future scenarios - Nemarundwe, N.; Jong, W. de; Cronkleton, P. (Center for International Forestry Research, 2003)
The purpose of this manual is to help trainers in future scenario better facilitate training workshops for field officers such as forestry managers, extension officers and researchers who are keen to facilitate future scenarios in their forest management projects. Future scenarios are a diverse and flexible set of methods that can be used to help forest user groups and decision makers define clear unified objectives, identify opportunities or obstacles in the path to their management goals, or prepare strategies and action plans for alternate future situations. This manual aims to encourage trainers or facilitators of future scenarios to be more reflective about how to structure their training workshop.